The Effect of Using Compound Exercises Using FT4A In Scoring In Youth Soccer Players Aged 17 – 18 Years Old - Mohammed, Saher (Journal of Physical Education, 2017)
The researcher used the experimental method. The subjects were 24 youth soccer players from Al Zewra and Al Shorta Club divided into two equal groups; Al Zewra group used compound exercises designed by FT4A while the second group used exercises designed without the FT4A. the research aimed at identifying the effect of using compound exercises using FT4A and compound exercises without FT4A in developing scoring in youth soccer players aged 17 – 18 years old. The researcher concluded that the first experimental groups developed better than the second in scoring after applying exercises designed using FT4A